Tracing Receptions of Etruscan culture in Italian and European Modernism (c. 1890-1950) - Verreth, Louis (Incontri. Rivista europea di studi italiani, 2024)
Review of: Chiara Zampieri, Martina Piperno & Bart Van den Bossche (eds.), Modern Etruscans. Close Encounters with a Distant Past, Leuven, Leuven University Press, 2023, 187 p., ISBN: 9789462703797, € 30,00 (also available in Open Access).